Influence of porosity on erosion behavior and hydrogen permeability of tungsten films - Glazunov, G.P.; Andreev, A.A.; Baron, D.I.; Bondarenko, M.N.; Causey, R.A.; Hassanein, A.M.; Konotopskiy, A.L.; Neklyudov, I.M.; Tarasov, I.K.; Volkov, E.D. (Физическая инженерия поверхности, 2006)
The erosion characteristics of dense and porous W-films deposited on Pd substrates were measured
under impact of mirror Penning discharge nitrogen plasma. It is shown that the erosion rate of high
porous tungsten films (up to 45% porosity) is similar to that for dense (1 – 3% porosity) tungsten
films. At the same time hydrogen permeation through porous tungsten films essentially higher than
for dense W coatings and in some cases it approaches to values as for bare Pd. The activation energies
of hydrogen permeability measured for two-layer Pd-W systems with high porosity are higher than
for dense W-films on Pd (15.44 kJ/mol and 12.8 kJ/mol, accordingly), but these values much lower
than the ones for bulk W under gas-driven permeation experiments. The possible reasons of such
erosion and permeation behavior are discussed. Зміряні ерозійні характеристики щільних і пористих плівок вольфраму на паладії при дії азотної
плазми відбивних розрядів Пеннінга. Показано,
що швидкість ерозії високопористих плівок вольфраму (пористість близько 45%) практично не
відрізняється від такої для щільних плівок W (пористість 1 – 3%). У теж час проникнення водню
крізь високопористі плівки вольфраму багато вище, ніж крізь щільні покриття W і в деяких випадках величини проникності можуть бути близькі
до такої для Pd без покриття. Енергії активації
водневої проникності зміряні для двошарових
систем Pd-W з високою пористістю W вище, ніж
для щільних W-плівок на Pd (15,44 кДж/моль і
12,8 кДж/моль, відповідно), але в обох випадках
ці величини багато нижче, ніж для масивного W
в умовах пронuкновения з молекулярної фази.
Обговорюються можливі причини такої поведінки ерозії і водневої проникності. Измерены эрозионные характеристики плотных
и пористых пленок вольфрама на палладии при
воздействии азотной плазмы отражательных разрядов Пеннинга. Показано, что скорость эрозии
высокопористых пленок вольфрама (пористость
около 45%) практически не отличается от таковой
для плотных W пленок (пористость 1 – 3%). В
тоже время проникновение водорода через высокопористые пленки вольфрама много выше, чем
через плотные W покрытия и в некоторых случаях величины проницаемости могут быть близки к таковой для Pd без покрытия. Энергии активации водородопроницаемости измереннные для
двухслойных Pd-W систем с высокой пористостью W выше, чем для плотных W-пленок на Pd
(15,44 кДж/моль и 12,8 кДж/моль, соответственно), но в обоих случаях эти величины много ниже, чем для массивного W в условиях проникновения из молекулярной фазы. Обсуждаются возможные причины такого поведения эрозии и
водородопроницаемости.